Containment systems : a design guide - Hirst, Nigel; Brocklebank, Mike; Ryder, Martyn (Institution of Chemical Engineers, 2002)
Annotation Covering the many types of containment systems available and the issues that must be considered when selecting a particular system for a specific duty, this title encompasses material properties, legal requirements, validation and operational and maintenance needs.
Keywords: Chemical processes -- Equipment and supplies.; Hazardous substances -- Transportation.; Chemicals -- Safety measures.; elektronické knihy; electronic books